Health and Nutritional Qualities of Drinks Produced in the Beninese Brewery Company and Those Sold on the Benin Market - TCHEKESSI, C. K. Célestin; Banon, Jultesse S. B.; Fagbohoun, Arthur; Aguenou, Tchouaib; Bouraima, Akim; SACHI, Pivot S. A.; Bleoussi, Roseline T. M.; Djogbe, Anayce A. M.; Assogba, Karl T.; AZOKPOTA, Paulin; BOKOSSA YAOU, Innocent Padonou (My University, 2021)
Aims: This study aims to evaluate the microbiological, physicochemical and sensory qualities of beverages sold on the market in Benin. Study Design: The biological material used consisted mainly of beverage samples (126) collected at random from three wholesalers at the points of sale on two different occasions (regular period of 15 days) at the Dantokpa international market in Cotonou (Benin) in between April and September 2019. Place and Duration of Study: This study was conducted between April and December 2019 at the Food Safety Research, Laboratory of Microbiology and Food Technologies, Department of Plant Biology, Faculty of Science and Technology, University of Abomey-Calavi, Benin. Methodology: Microbiological, physicochemical and sensory qualities of samples were evaluated. Results: The results of the microbiological analyzes revealed that all the drinks analyzed contained neither the total mesophilic aerobic flora, nor wild yeast, saccharomyces nor lactic bacteria. Therefore, the drinks are free from all pathogenic microorganisms that may harm the health of consumers. These products sold on the market complied with the criteria set by the standards and were therefore of satisfactory hygienic quality. However, the physicochemical parameters of the various drinks analyzed varied significantly from one brand to another. Results showed that the Nigerian Guinness produced contained more foam (287 s at 20 °C) and was rich in Diacetyl (0.119 mg / l) than the Benin Guinness (0.050 mg / l). As for the beer "La Béninoise", it produced more foam (220 s at 20 °C) than the Goldberg (209 s at 20 °C) but less than the Satzenbrau (250 s at 20 °C). The beer "La Béninoise" was less rich in Diacetyl (0.026 mg / l) and shown more than Goldberg (0.047 mg/l) and Satzenbrau (0.034 mg/l). As for the types of mixed drinks, it is the star Radler of Nigeria which presented a beautiful foam (235 s at 19.9 °C) with a cloudy aspect compared to the variegated one of Benin (227 s at 20.1 °C). Sensory analysis revealed that Beninese Brewery Company drinks were more appreciated by tasters. Conclusion: In view of these results, all the beverages analyzed can be recommended to consumers because most of these drinks are of satisfactory quality and consistent with the standards.
Keywords: Beer; soft drinks; motleys; consumers; quality